STORING DENTURES OVER NIGHT AND THE INFLUENCE ON BACTERIALS COLONIZATION OF ACRYLIC SURFACES - Maria Bolat; Dan Nicolae Bosînceanu; Nita Bogdan Vasile; Raluca-Elena Baciu; Balcos Carina; Dana Gabriela Budală (Romanian Dental Association for Education, 2022)
Introduction: As the adhesion of microorganisms to the surfaces of the dentures is a prerequisite for microbial colonization, the development of methods that can reduce the adhesion of C. albicans may represent a significant advance in the prevention of dentures-induced stomatitis. Although due to the increase in awareness about oral health care, the number of edentulous patients has decreased, but there are still a large number of denture wearers in countries such as Romania.